Accuracy of Hemoglobin Measurement Using Noninvasive Oxyhemoglobinometer in Pregnant Women at Health Center of Bantul District - Ratih Devi Alfiana; Hasballah Zakaria; Muhammad Nurhalim Shahib; Herman Susanto (Alma Ata University Press, 2018)
Iron deficiency anemia is a major health problem in pregnant women and has a detrimental effect on mothers and newborns. Given the consequences of anemia during pregnancy, an easy and accurate diagnosis is important. During this measurement of hemoglobin levels by involves taking the blood invasively, causing discomfort and trauma for the patient. Therefore, a hemoglobin level gauge is required using a non-invasive oxymeter system, in which the patient will be free of pain with minimal risk of infection and allow for the monitoring of the patient in critical condition. The purpose of this study was to compare the results of hemoglobin concentration using an oxyhemoglobinometer with automated hematology analyzer as gold standard to know the difference of result of accuracy. This study is a diagnostic test with cross sectional design. 78 normal pregnant women who checked their pregnancy at the center of health in Bantul district, each of them are examined their hemoglobin level by using the oxyhemoglobinometer and automated hematology analyzer as a comparison. For the different results were used pairwise t test, and with diagnostic test formula obtained accuracy values. There is a difference between the oxyhemoglobinometer tool with the average of 12.2 ± 1.7 and in the automated hematology analyzer obtained an average of 11.6 ± 1.2. With a value of p 0.001 which means there is a significant difference between the two tools. The results of the diagnostic test analysis obtained an accuracy of 69.2%. The oxyhemoglobinometer device cannot be used as an accurate measurement of hemoglobin levels, because the tool its low of accuracy